2016
DOI: 10.1590/0034-737x201663020019
|View full text |Cite
|
Sign up to set email alerts
|

Growth of sugar cane varieties under salinity

Abstract: RESUMOSubmitted on 02/20/2014 and approved on 01/20/2016 Growth of sugar cane varieties under salinityLarge salty areas in the Brazilian semi-arid region have limited farming in Northeastern Brazil. One example is the sugar cane cultivation, which reinforces the need of selecting varieties that are more tolerant to salinity. The objective of this study was to evaluate the effect of salinity on growth of ten varieties of sugar cane. The experiment was conducted in a greenhouse, set in the experimental field of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 11 publications
4
27
0
3
Order By: Relevance
“…They affirmed that only the variable Pol% sugarcane juice responded significantly to the irrigation system. Conversely, Simões et al (2015) and Neto et al (2006) found different results.…”
Section: Treatmentmentioning
confidence: 92%
See 1 more Smart Citation
“…They affirmed that only the variable Pol% sugarcane juice responded significantly to the irrigation system. Conversely, Simões et al (2015) and Neto et al (2006) found different results.…”
Section: Treatmentmentioning
confidence: 92%
“…investigated subsurface drip irrigation on sugarcane yield and quality, demonstrating that irrigation did not affect the technological traits in plant cane, disagreeing with the results obtained in this work. Simões et al (2015) evaluated different irrigation systems and reported that there was no influence on the technological quality of sugarcane. Neto et al (2006) studied the response of first ratoon sugarcane to irrigation levels and topdressing.…”
Section: Treatmentmentioning
confidence: 99%
“…The 3 dS m -1 value of the nutrient solution used in the cultivation of sugarcane was based on the studies of Trentin et al (2011), Boehringer et al (2013 and Batista et al (2015), and the amounts of NaCl in studies carried out with the aim of evaluating the effect of salinity on sugarcane growth (Plaut et al, 2000;Patade et al, 2011;Willadino et al, 2011;Simões et al, 2016). The EC monitoring was performed manually with a portable conductivity meter (CDH-42 model, Omega, Stamford, CT, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Agríc., Jaboticabal, v.37, n.5, p.940-952, sep./oct. 2017 941 and carotenoids (Santana et al, 2007;Willadino et al, 2011;Patade et al, 2011;Simões et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation